Integrated Thematic E-LKPD with RADEC- Based Neapod in Grade V Elementary School - Vianes Muliza Putri; Risda Amini (Universitas Pendidikan Ganesha, 2023)
The rapid development of science and technology makes integrated thematic learning in elementary schools use technology. However, the current LKPD only contains a collection of questions. The material is not structured and does not contain images that can attract students' interest. The existing LKPD is only a learning support, not a learning media. This research aims to produce E-LKPD products using the RADEC-based Nearpod application to keep abreast of existing technological developments and help students understand the material. This type of research is development research with the ADDIE development model. Methods of data collection, namely by interviews and documentation. Data collection instrument using a questionnaire. Data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The result of the research is that the average percentage of the assessment given by the teacher is 89% (very practical) and 87% students (very practical). The N-Gain score test was used to test the findings of the pre-test and post-test, and the results showed that the category was influential in the high category. Effectiveness can also be judged by how actively students are involved in their education. It was concluded that E-LKPD using the RADEC-based Nearpod application could improve student learning outcomes.